(untitled) - Sebesta, Robert W. (Boston, 1993)
Concepts of Computer Programming Languages introduces students to the fundamental concepts of computer programming languages and provides them with the tools necessary to evaluate contemporary and future languages. An in-depth discussion of programming language structures, such as syntax and lexical and syntactic analysis, also prepares readers to study compiler design.
Keywords: Programming languages (Electronic computers),Ngôn ngữ lập trình (Máy điện toán)